iPads/tablets and students with autism: A meta-analysis of academic effects. - Aspiranti, Kathleen B.; Larwin, Karen H.; Schade, Benjamin P. (Assistive Technology, 2020)
Since the introduction of iPads in 2010, educators have been working to effectively incorporate this technology as a supplement to curriculum and a tool to increase student engagement and student achievement. The current investigation examines the effectiveness of iPad applications in supporting the instruction of students identified on the autism spectrum. Specifically, this investigation provides a meta-analysis of available research that examines the use of iPad technology and its impact on learning outcomes for students with autism. Four studies were found that provided results for groups of students. The findings of this research are based on 12 effect-size measures, representing a synthesized sample size of 99 participants. The results suggest that the use of iPad technology can have a positive, significant effect on student learning outcomes. The moderators of these positive outcomes are presented and discussed.